2019
DOI: 10.1161/strokeaha.119.025054
|View full text |Cite
|
Sign up to set email alerts
|

R 2 eD AVM Score

Abstract: Background and Purpose— The management of unruptured brain arteriovenous malformations remains unclear. Using a large cohort to determine risk factors predictive of hemorrhagic presentation of arteriovenous malformations, this study aims to develop a predictive tool that could guide hemorrhage risk stratification. Methods— A database of 789 arteriovenous malformation patients presenting to our institution between 1990 and 2017 was used. A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 52 publications
(27 citation statements)
references
References 61 publications
0
26
1
Order By: Relevance
“…Survival analyses were conducted using the rms, version 6.3.0, 19 and survival, version 3.4.0, 20 packages for R software (R Foundation for Statistical Computing). Parameters in the R 2 eD score (except for race and ethnicity because the study population included only Chinese patients) were used to fit the model in our training set (data from the derivation cohort), and the DeLong test 14 was conducted to compare the ROCs between the R 2 eD-based model and our model. Data from the 3 cohorts were also used for external validation of the R 2 eD score to investigate its generalizability beyond its majority White population.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Survival analyses were conducted using the rms, version 6.3.0, 19 and survival, version 3.4.0, 20 packages for R software (R Foundation for Statistical Computing). Parameters in the R 2 eD score (except for race and ethnicity because the study population included only Chinese patients) were used to fit the model in our training set (data from the derivation cohort), and the DeLong test 14 was conducted to compare the ROCs between the R 2 eD-based model and our model. Data from the 3 cohorts were also used for external validation of the R 2 eD score to investigate its generalizability beyond its majority White population.…”
Section: Methodsmentioning
confidence: 99%
“…The R 2 eD score developed by Feghali et al 14 was the first scale to estimate the rupture risk of AVMs and was externally validated by Bird et al 15 This scoring system identified 5 risk factors from statistical models (race [non-White], exclusive deep location, small AVM size, exclusive deep drainage, and monoarterial feeding). However, this scale should be applied and interpreted with caution due to its cross-sectional data–based selection of risk factors and its lack of prospective validation.…”
Section: Introductionmentioning
confidence: 99%
“…or "STA-MCA bypass" is the most important neurosurgical treatment in the field of cerebral revascularization, and the majority of them have significant effects on the treatment and prognosis of moyamoya disease, for instance, the safety of STA-MCA bypass in the treatment of moyamoya disease (Liu et al, 2017), the hemodynamic problems of STA-MCA bypass in the treatment of moyamoya disease (Jeffree and Stoodley, 2009), the significance of Color Doppler monitoring of STA-MCA bypass in the treatment of moyamoya disease (Kawamata et al, 2011;Feghali et al, 2019). However, we employed keyword clustering analysis to determine the tight association within the cerebral revascularization research field.…”
Section: Hot Spots and Frontiersmentioning
confidence: 99%
“…In addition, the incidence of cerebral hyperperfusion has been estimated to range from 0.3 to 1.2% (Meyers et al, 2000), and it is regarded as a complication after carotid endarterectomy. Notably, transcranial Doppler (TCD), the only clinical device that can adequately assess cerebral hyperperfusion, provides a cerebral blood flow monitoring technology (Feghali et al, 2019). In addition, a number of studies indicate that, when performing superficial temporal artery/middle cerebral artery bypass surgery in elderly patients with moyamoya disease (Kim et al, 2022;Tsunoda et al, 2022), we must focus on strict blood pressure control and reduce the harmful cascade reaction caused by over perfusion during cerebral revascularization.…”
Section: Hot Spots and Frontiersmentioning
confidence: 99%
“…Most relevant studies have focused on finding predictors of BAVM hemorrhage from clinical features [4], [5], [8], [23], [36], [37]. Feghali et al developed a scoring model termed R2eD [36] based on multivariable logistic regression to detect hemorrhagic BAVMs based on race (nonwhite vs. white), exclusive deep location, BAVM size (small vs. large), venous drainage (exclusive deep vs. other), and monoarterial feeding (1 vs. >1 feeding artery). They used the hold-out method, in which half of the data was split as the validation data set to observe if the model was overfitting; the AUCROC was 0.685.…”
Section: Previous Modelsmentioning
confidence: 99%